Investigation of homotypic PYD and CARD domain interactions in ASC speck assembly - Otaş, Hasan Ozan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Apoptosis-associated speck-like protein containing a CARD (ASC) is a 22 kDa protein containing conserved PYD and CARD domains that belong to death-fold superfamily. Homotypic interactions between the domains occur via providing at least three certain surfaces of contact (Type I, II and III). ASC has an adaptor role between receptor and e ector proteins in the in ammation process having the ability to form a supramolecular globular complex called ASC speck through PYD and CARD homotypic interactions. When expressed in truncated form as PYD and CARD separately, these domains form lamentous structures. Apparently, these bers compact onto each other during the wild type ASC polymerization. In this study, our aim was to elucidate the importance of speci c locations on PYD-PYD and CARD-CARD interaction surfaces during the polymerization process. E ects of 19 single and 22 double mutations were observed introducing them on important residues such as E13A, D48A, Y60A, E130A, Y146A, R150A and M159A to hit one and/or two interaction surfaces at the same time. E ects of the mutations were visualized using uorescence and confocal microscopy to qualify the change in the level of organization of the phenotype from lamentous to soluble. Next, we analyzed rate of homooligomerizations in mutant sets using FRET technique to quantify the interaction e ciencies in presence of disruptive mutations. Our results showed that PYD mutants, which've been known to disrupt homooligomerization, are able to provide multimeric lamentous structures when expressed together with their wild type counterparts although CARD mutants have less tolerance to mutations in the interaction surfaces. We identi ed certain mutations that increase, decrease or block FRET signal. Our study provides better explanation and new insights about the oligomerization dynamics of the in ammasome complex.
Keywords: Apoptosis.